Ethnomedical inventory of aromatic and medicinal plants in central area of Morocco: Comparative analysis of urban zones and the interactions between plant material, preparation, and administration approaches - Jaouad, Noura; Soussi, Meriem; Tazi, Ahmed; Maache, Souad; Afqir, Hajar; Hajji, Said; Zerkani , Saida; Errachidi , Faouzi; Taleb, Mustapha (Ethnobotany Research and Applications, 2025)
Background: In this paper, we conducted an ethnomedicinal survey of the medicinal plants used in the central urban regions of Morocco (Middle Atlas and Saiss Plain). We aimed to evaluate the diversity of medicinal plants and their variability between big cities and small municipalities. Then, we searched the relationships between plants, treated illnesses, used parts, and preparation modes. Methods: Field visits were conducted in eight urban cities divided into big and small cities during 2017-2018 and 2019-2020. A questionnaire containing sociodemographic features, medicinal plants, used parts, and preparation modes was used to collect data. Descriptive and multidimensional statistics were used to compare the studied parameters and to investigate their relationships. Results: In total, 155 plants were used by participants, with a higher number in small towns (n=149) compared to big cities (n=100). Most participants (62%) combined modern and traditional treatments. Sociodemographic features, including age, gender, education, and profession, were significantly variable and impacted the used species, treated diseases, used parts, and preparation modes. Further, 21 disease groups were treated based on different parts (n=14) and preparation modes (n=9). Multivariate analysis showed that the medicinal plants, used parts, preparation modes, and treated diseases were correlated. These data are new, fill the gap of medicinal plants in urban areas of Morocco, and offer valuable results for laboratory assays. Keywords: Ethnobotany, diversity and variability of plants, urban areas, central Morocco, traditional medicine